The Combination of Nitrogen (N2) Pyrolysis and Carbon Dioxide (CO2) Activation for Regenerating Spent Activated Carbon - Ya-Chen Ye; Wen-Shing Chen; Chi-Hung Tsai; Wen-Tien Tsai (Applied Sciences)
In line with the principles of the circular economy, this study aimed to develop a pyrolysis-activation regeneration process capable of producing highly porous carbon materials from spent granular activated carbon (GAC), which was generated by a high-tech electronics manufacturing company in Taiwan. Thermogravimetric analysis (TGA) and other thermochemical analyses were first conducted to investigate the thermal decomposition behavior of the spent GAC. Subsequently, the thermal regeneration system was employed to perform the N2 pyrolysis and CO2 activation experiments under various process conditions (i.e., 800, 850, and 900 °C for holding 0, 30, and 60 min, respectively). Analytical instruments included a surface area and porosimeter for pore property analysis, scanning electron microscopy (SEM) for porous texture observation, and energy dispersive X-ray spectroscopy (EDS) for surface elemental distribution analysis. The results revealed that the pore properties of thermally regenerated GAC were significantly improved compared to the spent GAC, indicating the effective removal or decomposition of adsorbed organics and deposited substances under the process conditions. Additionally, thermal regeneration via physical activation with CO2 led to enhanced pore properties compared to simple pyrolysis. The maximum BET surface area achieved exceeded 720 m2/g, which was greater than those of spent GAC (approximately 425 m2/g) and N2-pyrolyzed GAC (approximately 570 m2/g) under the same regeneration conditions (i.e., 900 °C with a 30 min holding time).